Evaluating organisational performance in healthcare: a mixed-method study using the McKinsey 7S framework - Houda Bennani; Imane Bounjerte; Sara Khalidy; Ilham Mazouzy; Joumana El Turk; Ibtisam Haidar; Anass Kettani; Rachid Saile (BMJ Open Quality)
Background The Moroccan healthcare sector faces numerous quality challenges. Therefore, various strategies—such as the implementation of quality management systems (QMSs)—were put into practice to improve the quality of care and reinforce the healthcare system. Among these, ISO 9001 represents one formalised QMS framework. Despite its increasing adoption, only a few studies have attempted to evaluate how ISO 9001-certified QMSs influence hospital performance and effectiveness. Our study aimed to fill this gap by exploring the impact of an ISO 9001-certified QMS on organisational performance in a hospital centre in Casablanca, Morocco.Methods Initially, we employed the McKinsey 7S model as a diagnostic tool to evaluate organisational performance across seven key dimensions. Data were collected via structured interviews and a questionnaire administered to hospital staff. Additionally, clause 9 of the ISO 9001:2015 standard—focused on performance evaluation—was used to assess the QMS implementation. As for data analysis, the software Sphinx V5 was used for data entry, and IBM SPSS Statistics V.25 was used for reliability analysis and non-parametric tests.Results The results indicated a positive staff perception of the QMS’s performance and its impact on patient satisfaction, continuous improvement and overall hospital effectiveness. The results also highlighted gaps in organisational factors such as internal communication and staff training, suggesting areas for future improvement.Conclusions This study provided a dual-framework approach to evaluating and enhancing hospital performance by integrating ISO 9001 standard requirements with the McKinsey 7S model. The findings show the value of combining a formal QMS (ISO 9001) with organisational diagnostic tools (7S Model) in understanding and driving quality improvements in healthcare settings.